BRAFAMP Frequently Co-occurs With IDH1/2, TP53, and ATRX Mutations in Adult Patients With Gliomas and Is Associated With Poorer Survival Than That of Patients Harboring BRAFV600E - Da, Rong; Wang, Maode; Jiang, Haitao; Wang, Tuo; Wang, Wei (Frontiers in Oncology, 2021)
Abnormal RAS/RAF signaling plays a critical role in glioma. Although it is known that V600E nutation of v-raf murine viral oncogene homolog B1 (BRAFV600E) and BRAF amplification (BRAFAMP) both result in constitutive activation of the RAS/RAF pathway, whether BRAFV600E and BRAFAMP have different effects on the survival of glioma patients needs to be clarified. Using cBioPortal, we retrieved studies of both mutations and copy number variations of the BRAF gene in CNS/brain tumors, and investigated data from 69 non-redundant glioma patients. The BRAF mutation group had significantly more male patients (64.00% vs. 36.84%; P = 0.046), and a higher occurrence of glioblastoma multiforme (66.00% vs. 31.58%; P = 0.013) compared to those in the other group. The BRAFAMP group had significantly more patients with the mutant isocitrate dehydrogenase 1 and 2 (IDH1/2) (73.68% vs. 18.00%; P = 0.000), tumor protein p53 (TP53) (73.68% vs. 30.00%; P = 0.002), and alpha thalassemia/mental retardation syndrome X linked (ATRX) (63.16% vs. 18.00%; P = 0.001) than the mutation group. The BRAFAMP & IDH1/2WT cohort had lower overall survival compared with the BRAFAMP & IDH1/2MT groups (P = 0.001), and the BRAF mutation cohort (P = 0.019), including the BRAFV600E (P = 0.033) and BRAFnon-V600E(P = 0.029) groups, using Kaplan–Meier survival curves and the log rank (Mantel-Cox) test. BRAFAMP & IDH1/2WT genotype was found to be an independent predictive factor for glioma with BRAF mutation and BRAFAMP using Cox proportional hazard regression analysis (HR = 0.138, P = 0.018). Our findings indicate that BRAFAMP frequently occurs with IDH1/2, TP53, and ATRX mutations. Adult patients with glioma with BRAFAMP & IDH1/2WT had worse prognosis compared with those with BRAF mutation and BRAFAMP & IDH1/2MT. This suggests that the assessment of the status of BRAFAMP and IDH1/2 in adult glioma/glioblastoma patients has prognostic value, as these patients have relatively short survival times and may benefit from personalized targeted therapy using BRAF and/or MEK inhibitors.